Low-temperature combustion synthesis of Bi2WO6 nanoparticles as a visible-light-driven photocatalyst - Zhang, Zhijie; Wang, Wenzhong; Shang, Meng; Yin, Wenzong (Journal of hazardous materials, 2010)
Visible-light-induced Bi(2)WO(6) photocatalyst has been successfully synthesized via a facile low-temperature combustion synthesis method, using glycine as the fuel. The photocatalytic activities of the as-synthesized samples were evaluated by the photodegradation of rhodamine B (RhB) and phenol under visible-light irradiation (lambda>420 nm). The results showed that the molar ratio of fuel to oxidizer had an important influence on the photocatalytic activities of the products. When the molar ratio of fuel to oxidizer was 1, the photocatalyst exhibited the highest degradation efficiency, which can completely degrade RhB with a concentration up to 10(-4)M within 75 min. Besides decoloring, the markable reduction of chemical oxygen demand (COD) was also observed in the degradation of RhB, further demonstrating the photocatalytic performance of Bi(2)WO(6). Additionally, the photocatalyst showed much enhanced visible photocatalytic efficiency, up to 94.2% in 4h, than the bulk Bi(2)WO(6) powder (SSR) in the degradation of phenol.